2021
DOI: 10.1155/2021/6615937
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis and Numerical Simulation Study on Main Controlling Factors of Surface Movement and Deformation in Strip Filling Mining under Thick Unconsolidated Layers

Abstract: In many mining areas, there is a lot of pressed coal under buildings, railways, and water bodies, and there are geological conditions of thick unconsolidated layers, so the surface subsidence has certain particularity. The key to solve the problem of pressed coal is the control technology of surface subsidence. The development of strip filling technology provides a kind of economical and effective surface subsidence control technology. With the passage of time, the natural weathering, flow, and fracture of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thick loose strata mostly consist of sparsely distributed sediments that have not undergone the process of solidification and hardening into rock, exhibiting comparable physical characteristics [9]. The underlying rock strata, situated beneath the extensive loose strata, are composed of sequentially deposited mudstone, fine sandstone, siltstone, and other stones exhibiting distinct physical features [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thick loose strata mostly consist of sparsely distributed sediments that have not undergone the process of solidification and hardening into rock, exhibiting comparable physical characteristics [9]. The underlying rock strata, situated beneath the extensive loose strata, are composed of sequentially deposited mudstone, fine sandstone, siltstone, and other stones exhibiting distinct physical features [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the width of the filling body had a great influence on the stability of the gob-side roadway. Sun et al [27] studied the deformation characteristics of fully mechanized caving roadways through similar simulation tests, concluding that the filling body should be of both a certain strength and a certain deformation resistance capacity. Seryakov [28] analyzed the deformation and stress distribution characteristics of roadway surrounding rock and proposed a design principle for deep roadway filling support by analyzing on-site mine pressure monitoring data.…”
Section: Introductionmentioning
confidence: 99%